ANALISIS HEALTH BELIEF MODEL TERHADAP KESEDIAAN MELAKUKAN VAKSINASI HUMAN PAPILLOMAVIRUS SEBAGAI UPAYA PENCEGAHAN KANKER SERVIKS PADA PEGAWAI PEMERINTAHAN KABUPATEN SUKABUMI TAHUN 2022 - Aninda Nurul Lita (2022)
The high cases of cervical cancer as the second most common cancer in Indonesia require attention and primary prevention efforts for everyone. In view of the appeal from the Ministry of Health regarding HPV vaccination which will be mandatory as an effort to reduce cervical cancer rates in Indonesia. This study aims to analyze the health belief model factors that influence the willingness to do HPV vaccination as an effort to prevent cervical cancer in female employees in the Sukabumi Regency government in 2022. This study uses a quantitative method with a cross-sectional design. Data was collected through filling out questionnaires by 213 respondents from 479 employees. The result was 50.7% of respondents were willing to do HPV vaccination. There is a relationship between perceptions of susceptibility, benefits, barriers, cues to action, and self-efficacy with the willingness to do HPV vaccination among employees in Sukabumi district government. Meanwhile, the perception of severity was not related to the willingness to do HPV vaccination. In the multivariate analysis, it was found that cues to action (POR=5,477; 95% CI=2,6-11,2) had the most influence on willingness to do HPV vaccination. It is hoped that the government of Sukabumi Regency will make this research an input for make a health promotion program for every agency regarding cervical cancer, especially HPV vaccination.